A novel digital distance relaying technique for transmission line protection. - Eissa, M.M (IEEE Transactions on power delivery)
Parallel transmission lines often pose more difficult protection problems than single lines. In the case of parallel lines, a number of problems arise when using the distance protection. The paper discusses problems associated with parallel line distance relaying schemes and presents a novel technique to overcome these problems. Two relays instead of four are proposed for the double lines, One relay is located at the beginning and another one at the end. Each relay is fed by three voltage and six current signals from the two lines. The suggested technique is based on the comparison of the measured impedance of corresponding phases. So, the complexity of the possible types of faults, high path fault resistance, mutual effects, current in-feed, inter-system faults are solved. Moreover, 100% of line is protected and the problem of balance-point locations is avoided. Alternative Transient Program models the power system and simulates different fault conditions